2019
DOI: 10.1002/mp.13660
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Simulation of dose buildup in proton pencil beams

Abstract: Purpose The purpose of this study is to characterize the magnitude and depth of dose buildup in pencil beam scanning proton therapy. Methods We simulate the integrated depth–dose curve of realistic proton pencil beams in a water phantom using the Geant4 Monte Carlo toolkit. We independently characterize the electronic and protonic components of dose buildup as a function of proton beam energy from 40 to 400 MeV, both with and without an air gap. Results At clinical energies, electronic buildup over a distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…400 µm and for 220 MeV protons of approx. 1100 µm . This proves that the settings used here in TOPAS were well comparable with the previous publications and further support our experimental data.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…400 µm and for 220 MeV protons of approx. 1100 µm . This proves that the settings used here in TOPAS were well comparable with the previous publications and further support our experimental data.…”
Section: Discussionsupporting
confidence: 91%
“…The maximum range of the electrons was 0.8 mm in C2F4 and 1.5 mm if converted to tissue equivalent depth. In general, an exact range limit of an electron buildup can hardly be defined due to the overlap with the nuclear buildup and was found mostly empirically …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Medical Physics recently published an article by Kelleter et al who also performed simulations of the dose buildup effects of proton pencil beams. 2 Kelleter et al compare their findings to ours and claim, "In contrast to what was found by Pfuhl et al we do not see evidence that particles with A > 1 contribute to the buildup effect on the short or the long length scale." This sentence is misleading to the reader, which is why we would like to clarify the issue in this letter.…”
Section: Dear Editorcontrasting
confidence: 67%